2012
DOI: 10.1021/mp3002528
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Virus-Based Macrofluorogenic Probes Target Azide-Labeled Surface Glycans in MCF-7 Breast Cancer Cells

Abstract: Chemical addressability of viral particles has played a pivotal role in adapting these biogenic macromolecules for various applications ranging from medicine to inorganic catalysis. The consistent multimeric assemblies dictated by its genetic code, facile large scale production, lack of observable toxicity in humans, Cowpea mosaic virus possesses multiple features that are advantageous for the next generation of virus-based nanotechnology. Herein, the chemistry of the viral particles is extended with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In order to facilitate the development of the magnetic isolation protocol, 2% DMSO treated cells as negative control were introduced into our system. Many reports indicated that DMSO treatment could induce the differentiation of stem cells. , Before we used it as a negative control, we compared the tumor sphere formation efficiency (SFE) and soft-agar colony formation efficiency (CFE) of DMSO treated cells versus normal culture cells. SEF and CFE were well-established in vitro assays for identifying CSCs. , Sphere formation and clonogenic efficiency were calculated as the number of spheres or colonies divided by the number of cells seeded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to facilitate the development of the magnetic isolation protocol, 2% DMSO treated cells as negative control were introduced into our system. Many reports indicated that DMSO treatment could induce the differentiation of stem cells. , Before we used it as a negative control, we compared the tumor sphere formation efficiency (SFE) and soft-agar colony formation efficiency (CFE) of DMSO treated cells versus normal culture cells. SEF and CFE were well-established in vitro assays for identifying CSCs. , Sphere formation and clonogenic efficiency were calculated as the number of spheres or colonies divided by the number of cells seeded.…”
Section: Resultsmentioning
confidence: 99%
“…Many reports indicated that DMSO treatment could induce the differentiation of stem cells. 35,36 Before we used it as a negative control, we compared the tumor sphere formation efficiency (SFE) and soft-agar colony formation efficiency (CFE) of DMSO treated cells versus normal culture cells. SEF and CFE were well-established in vitro assays for identifying CSCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the uorescent signal appears only upon the linkage between the virus and the dye, so any unconjugated dye contributes little to the uorescence and no false positive signal is observed. 44 Small organic molecules with uorescence emission are also used in labeling the internal components of virions. But for intact virions, it is difficult to label internal viral components, typically nucleic acid, for they are inaccessible to dye attachment once incorporated into the virion.…”
Section: Progress Of Chemical and Physicochemical Labeling Methodsmentioning
confidence: 99%
“…Therefore, using bioorthogonal chemical conjugation could be a promising strategy for in vivo cancer targeting. 25 32 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using bioorthogonal chemical conjugation could be a promising strategy for in vivo cancer targeting. [25][26][27][28][29][30][31][32] Oxime ligation is a highly efficient click-type bioorthogonal condensation reaction between an oxyamine and an aldehyde or a ketone. 11,18,33 The formed oxime is highly stable toward hydrolysis (K d # 10 À8 M) compared with the corresponding imines or hydrazones.…”
Section: Introductionmentioning
confidence: 99%